Alat kendali perangkat listrik berbasis Arduino Mega - Yunus Tjandi; Soetyono Iskandar (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Improper installation of electricity and does not meet the PUIL standards will make large loss to consumers. The objectives of this Community Partnership Program (PKM) are: (1) to increase knowledge of teachers and students in SMK National and SMKT Somba Opu in manufacturing Arduino Mega-based monitoring and control system software to monitor and control the electrical devices of a building, (2) to improve the skills of teachers and students of SMK National and SMKT Somba Opu in making and utilizing Arduino Mega-based monitoring and control tools to monitor and control electrical equipment of a building, and (3) to improve the skills of teachers and students of SMK National and SMKT Somba Opu in making the interface and application of Arduino Mega-based control system to monitor and control the electrical equipment of a building. The method used in this workshop are of lectures, discussions, question and answer session and demonstrations. The results of this program show that (1) the teachers and students' knowledge in making Arduino Mega-based monitoring and control system software for monitoring increased, (2) the teachers and students' skills increased in making and utilizing Arduino Mega-based Monitoring and Control Tools for monitoring and controlling electrical devices for building, (3) the teachers and students' skills are improved in creating an interface and application of Arduino Mega-based monitoring and control tool to monitor and control the electrical devices of a building, so that the device can be controlled using a smartphone at close range or from a distance.